Nasehat Dalam Serat Empu Tangguling Wesi Aji Dan Relevansinya Terhadap Ajaran Agama Islam - Mareta Dwi Gandini; Respati Retno Utami (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to find out the advice contained in Serat Empu Tangguling Wesi Aji and the teachings in Islam. The advice in the Islamic religious principles and teachings can be used as a guide in living everyday life. And as proof that in all forms of teaching, wherever the time, humans are always taught to do good.